2016
DOI: 10.3390/ijms17091548
|View full text |Cite
|
Sign up to set email alerts
|

Dose and Radioadaptive Response Analysis of Micronucleus Induction in Mouse Bone Marrow

Abstract: Enhanced cellular DNA repair efficiency and suppression of genomic instability have been proposed as mechanisms underlying radio-adaptive responses following low-dose radiation exposures. We previously showed that low-dose γ irradiation does not generate radio-adaptation by lowering radiation-induced cytogenetic damage in mouse spleen. Since radiation may exert tissue-specific effects, we extended these results here by examining the effects of γ radiation on cytogenetic damage and proliferative index in bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 78 publications
2
6
0
Order By: Relevance
“…In the present study, fractionated doses of 0.5 and 1 Gy administered to mice for 1 or 2 weeks induced MN both in the bone marrow and in peripheral blood RET. Induction of micronuclei in reticulocytes or polychromatic erythrocytes in mouse bone marrow or peripheral blood in vivo following irradiation were also observed previously at different doses and times of irradiation (Gandhi 2013; Bannister et al 2016; Dobrzyńska et al 2016). The frequency of micronuclei was similar for 0.5 Gy and lower for 1 Gy as compared to our earlier study, where the same doses of irradiation were used (Dobrzyńska et al 2016).…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, fractionated doses of 0.5 and 1 Gy administered to mice for 1 or 2 weeks induced MN both in the bone marrow and in peripheral blood RET. Induction of micronuclei in reticulocytes or polychromatic erythrocytes in mouse bone marrow or peripheral blood in vivo following irradiation were also observed previously at different doses and times of irradiation (Gandhi 2013; Bannister et al 2016; Dobrzyńska et al 2016). The frequency of micronuclei was similar for 0.5 Gy and lower for 1 Gy as compared to our earlier study, where the same doses of irradiation were used (Dobrzyńska et al 2016).…”
Section: Discussionsupporting
confidence: 75%
“…It was reported that MN formation is induced 48–72 h after irradiation [29]. In the present study, induction was still observed 3 weeks after irradiation, as well as the inhibition of induction by DADS.…”
Section: Discussionsupporting
confidence: 72%
“…This indelicate segregation of chromosomes may result from hypo-methylation of repeat sequences present in DNA, dysfunctional spindle apparatus, or irregularities in kinetochore proteins or their assembly. The resulting MN frequency could potentially arise to increased DNA repair proficiency, a decrease in the number of cellular DNA double strand breaks, an increase in cellular proliferative index, increased apoptosis of erythroblasts, or harboring DNA damage, based on the length of the erythrocyte cell cycle [35,36].…”
Section: Effect Of C Freundii Bacteriocin On Mn Frequencymentioning
confidence: 99%